ESP32 MICROCONTROLLER IMPLEMENTATION FOR MONITORING WATER QUALITY AND LEVEL IN A HYDROPONIC SYSTEM: A CASE STUDY AT AZIZ HYDROPONIC GARDEN, CIAMIS - Zaman, Fanji Fakhru; Agnia, Gina Fauziah (RISTEC : Research in Information Systems and Technology, 2025)
Hydroponic farming is a method of cultivation that uses water enriched with nutrients essential for plant growth. This method produces high-quality crops as it eliminates the need for chemical fertilizers, pesticides, and other plant treatment substances. Moreover, the risk of pest and disease attacks is significantly reduced since soil is not used. Hydroponic systems have become a practical alternative for urban farming in areas with limited land. At the research site, the current issue is that plant monitoring is still conducted manually. Garden managers must regularly check each plant block, which results in inefficient time usage. Therefore, to address this issue, a prototype of a monitoring system for water quality and water level in hydroponic plants is needed. This system utilizes Internet of Things (IoT) technology integrated with the ThingSpeak server to enable efficient plant monitoring. A pH sensor module is used to measure the nutrient content of the water, and a water level sensor is used to detect the water height in the reservoir. The control commands are then processed by an ESP32 microcontroller on an Arduino board. The sensor data is automatically recorded on the ThingSpeak server every 15 seconds in the form of graphs and numerical sensor values, allowing garden managers to monitor the system using a computer device.